The impact of relationship learning and absorptive capability on innovation performance based on employees perception ; evidence in Zain Company - Aliyadeh, Rania (My University, 2022)
En iyi organizasyonlar, faaliyet gösterdikleri çevrede hakim olan temellere göre yenilik yapma kabiliyetine sahip olan, bununla birlikte bu çevredeki hızlı değişimlerin getirdiği zorluklarla başa çıkmak için stratejik yeteneklere sahip olanlardır. Güçlü yönlerine dayalı olarak bilgi birikimini ve kaynaklarının optimal kullanımını geliştirir. Zayıf yönleri, fırsatları ve tehditleri, iş ortamlarındaki faaliyetlerini karakterize eder, bu da onların üstünlük elde etmelerini ve dış değişikliklere uyum sağlamalarını ve eğitimli organizasyonlar olmalarını sağlar. Bu çalışmanın amaçlarına göre, ilişkisel öğrenme ve özümseme yeteneğinin inovasyon performansı üzerindeki etkisi ölçülecek ve analiz edilecektir. Ürdün Amman'daki Zain şirketindeki çeşitli departmanların tüm yöneticileri ve uzmanları, çalışma topluluğunun üyeleridir. Çalışmanın amaçlarına ulaşmak ve hipotezlerini test etmek için, veri toplama için birincil araç olarak bir anket geliştirilecek ve işlemek için korelasyon katsayısı analizi de dahil olmak üzere çeşitli istatistiksel yöntemler kullanılacaktır.

The best organizations are those that have the ability to innovate according to the prevailing foundations in the environment in which they operate, in addition to having strategic capabilities to deal with the challenges posed by rapid changes in this environment, through the ability to deal with and develop knowledge and optimal use of its resources based on its strengths Their weaknesses, opportunities and threats characterize their activities in their business environment, which allow them to achieve superiority and the ability to adapt to external changes and become educated organizations. According to the objectives of this study, the impact of relationship learning and absorptive capability on innovation performance will be measured and analysed. All managers and specialists of several departments in Zain company in Amman, Jordan, are members of the study community. In order to achieve the study's objectives and test its hypotheses, a questionnaire will be developed as the primary tool for data collection, and a variety of statistical methods, including correlation coefficient analysis, will be used to process.
Keywords: Absorptive capability; Başarı, İşletmelerde; Executive ability; Innovation performance; İlişki öğrenimi; Leadership; Liderlik; özümseme yeteneği; Performance; Performans; Portfolio management; Portföy yönetimi; Psikolojik yönleri; Psychological aspects; Relationship learning; Success in business; yenilik performansı; Yönetici yeteneği; Zain company; Zain şirketi